PENERAPAN MAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA DENGAN METODE HIRADC PADA PLTGU TAMBAK LOROK SEMARANG - Afrida Hafshalya Riandini; Muhammad Sagaf; Akhmad Syakhroni (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Overhaul activities, especially plate disassembly and installation (replacement expansion joint No.6) involve a lot of labor, have a high working intensity, and use diverse work equipment. In this work process, it is carried out manually handled by a total of 9-13 daily workers and there is a process of lifting expansion joint plates with a length and width of at least 5 meters with a plate weight of 1500 kg so that with a heavy and diverse workload it is necessary to ensure occupational safety and health (K3) of the workers. This work has the possibility of a risk of work accidents from mild to severe scale if a good K3 Management System (SMK3) is not carried out. SMK3 has a role in reducing the level of risk using appropriate risk control as well as being implemented so that workers can work safely and comfortably. Hazard Identification Risk Assessment and Determining Control (HIRADC) is one of the methods in the risk management system regulated in OHSAS 18001:2007 in clause 4.3.1 and hazard control based on a hierarchy of risk control measures is based on ISO 45001:2018. The results of this study were from 11 activities with 32 job descriptions after identification of hazards in terms of the work environment, labor, and tools used as well as risk assessment there was an initial risk level to an extreme scale. Thus, it is necessary to handle and recommend in the form of qualitatively descriptive hazard/risk control from K3 management in the workplace to create a safe and comfortable work environment and can reduce the level of risk that exists.